Unveiling the power of Pueraria lobata: a comprehensive exploration of its medicinal and edible potentials - Kou, Baixin; Meng, Lingkun; Zhao, Mengya; Wang, Haidong; Lu, Chunyang; Yan, Mingming; Li, Guangzhe (Frontiers in Pharmacology, 2025)
BackgroundPueraria lobata (Willd.) Ohwi, a perennial vine native to China, has significant medicinal and edible value. Its roots are used as medicine and are known as kudzu (Chinese: Gegen) and were first recorded in Shen Nong Ben Cao Jing. In addition, its roots and powder can be made into food.Aim of the studyTo integrate information on the source of Pueraria lobata (PL), summarize the evolution of its medicinal and edible value, and generalize its chemical composition, biosynthetic pathways, metabolism, and biological activity.Materials and MethodsA comprehensive literature search (1975–2025) was conducted across ScienceDirect, Google Scholar, PubMed, Web of Science, CNKI, WFO (www.worldfloraonline.org), MPNS (https://mpsn.kew.org), Changchun University of Chinese Medicine Library collections, and SciFinder. Ancient applications were validated through analysis of classic Chinese medical literature.ResultsPL is predominantly found in Asia, Europe, and America, with significant populations in China’s Zhejiang, Jiangxi, Jiangsu, Guangdong, and Guangxi provinces. The plant comprises flavonoids, triterpenoids, and coumarins, including isoflavonoids like daidzein and puerarin, which are synthesized via diverse pathways. Metabolites produced from liver or intestinal reactions are crucial to PL’s effectiveness. Key components include puerarin, daidzein, genistein, biochanin A, and formononetin. In China, PL is incredibly versatile, being used in a wide range of foods, teas, preservatives, dairy products, etc.ConclusionIts extensive biological activities benefit the human body, with particular emphasis on liver protection, anti-osteoporosis, and anti-diabetic effects. These attributes highlight the potential for developing health foods, revealing PL’s promising prospects in the pharmaceuticals and nutritional healthcare industries.